Agonist of the adenosine A3 receptor, IB-MECA, and inhibitor of cyclooxygenase-2, meloxicam, given alone or in a combination early after total body irradiation enhance survival of γ-irradiated mice - Hofer, Michal; Pospíšil, Milan; Dušek, Ladislav; Hoferová, Zuzana; Komůrková, Denisa (Radiation and environmental biophysics, 2014)
There exists a requirement for drugs which would be useful in therapy of an acute radiation damage of a mammalian organism. The aim of the study was to evaluate survival parameters in mice exposed to a lethal γ-ray dose of 8.5 Gy and treated with single doses of an adenosine A(3) receptor agonist, IB-MECA, or a cyclooxygenase-2 (COX-2) inhibitor, meloxicam, administered alone or in a combination early after irradiation, i.e., 0.5 and 1 h post-irradiation, respectively. The assessed parameters were the mean survival time (MST) and the cumulative percentage 30-day survival (CPS). Administrations of single intraperitoneal doses of either IB-MECA 0.5 h post-irradiation or meloxicam 1 h post-irradiation resulted in statistically significant increases of MST in comparison with the control irradiated mice. Combined administration of IB-MECA and meloxicam was found to be the only treatment statistically enhancing the parameter of CPS and to lead to the most expressive increase in MST of the experimental mice. The findings add new knowledge on the action of an adenosine A3 receptor agonist and a COX-2 inhibitor in an irradiated mammalian organism and suggest the potential of both the investigated drugs in the treatment of the acute radiation damage.
Keywords: Male; receptor adenosinový A3; lékové interakce; Cyclooxygenase 2; Time Factors; Animals; míra přežití; Meloxicam; časové faktory; Drug Interactions; Mice; Thiazoles; Adenosine A3 Receptor Agonists; adenosin; Survival Rate; agonisté adenosinového receptoru A3; thiazoly; mužské pohlaví; Receptor, Adenosine A3; Radiation-Protective Agents; thiaziny; celotělové ozáření; Cyclooxygenase 2 Inhibitors; Gamma Rays; inhibitory cyklooxygenasy 2; radioprotektivní látky; cyklooxygenasa 2; zvířata; Thiazines; Adenosine; meloxikam; Whole-Body Irradiation; záření gama; myši